Another story of the daily circulation of Özgür Gündem : affective materiality - Bayram, Sidar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
This thesis aims to tell the story and history of the daily newspaper Özgür Gündem in the first half of the 1990s, by focusing on the everyday practices organized around the circulation of the newspaper, in order to track down in which ways Özgür Gündem as a material affected the capacities of other bodies and materials to act and relate. As the first alternative press writing on the Kurdish problem in Turkey, Özgür Gündem's circulation carved out a space for the confrontation between the state targeting the circulation of Özgür Gündem and the newspaper community who exposed themselves to state violence for enabling its circulation. The affective density of Özgür Gündem, which exposed the bodies to state violence is analyzed in terms of the affective economies of sorrow (an affect which diminishes the power to live) activated by state violence and of joy (an affect which increases the power to endure) activated by sublimation. The antagonistic character of the affective economies of sorrow and joy constituted alongside the circulation of Özgür Gündem, points towards the ways in which Özgür Gündem intensified practices of state violence while trying to organize a voice against them. From 1992 to 1995, its circulation left behind several bodies dead, disappeared, tortured, humiliated, imprisoned, shops burned down, buildings blown up and so on. This process coupled with increasing censorship, the introduction of MED TV and the radicalization of the newspaper's attitude; the conjuncture of all these processes resulted in the drastic decrease in Özgür Gündem's affective capacities. While Özgür Gündem's successors continued to be published with different names, the generic name for all of them is still known as Özgür Gündem. The story and history of Özgür Gündem is that of a historical gesture for witnessing and communicat
Keywords: Freedom of the press -- Turkey.; Press and politics.